Ta’lîm al-Lughah al-‘Arabiyyah bi Tarjamah Âyât al-Fâtihah wa Awâili al-Baqarah - Rijal Mahdi (Postgraduate of IAIN Metro Lampung Indonesia, 2022)
This study aims to reveal the possibility of using interpretation books to teach Arabic to speakers of other languages, by translating the meanings of the verses of the Holy Quran into a verse in order to find out the meanings of the Word of Allah directly. This research has taken an analytical approach in order to identify the objective of the subject of the research on al-Fatihah and early al-Baqarah. It has been found that many words in the early al-Baqarah are repeated more than one position, without going into the differences and uses of the word, but only knowing the overall meanings of the translated word in consideration of the backgrounds of learners and listeners committed to attending weekly lessons as well as taking into account the ages of applicants. The researcher has reached several conclusions, the most important of which is that it is possible to use Quranic interpretation in the teaching of Arabic language, especially for religious purposes for the general public, because such books are related to people's daily lives. This Quranic interpretation has specifically helped learners understand their repetitive language patterns and because the al-Baqarah contains duplicate words, enabling attendees to understand their meanings once without any fatigue on one side, and helping them to translate duplicate words in the other verse.